Longer charged amino acids favor β‐strand formation in hairpin peptides. (10th June 2021) - Chang, Jing‐Yuan; Li, Nian‐Zhi; Wang, Wei‐Ming; Liu, Chih‐Ting; Yu, Chen‐Hsu; Chen, Yan‐Chen; Lu, Daniel; Lin, Pei‐Hsuan; Huang, Cheng‐Hsin; Kono, Orika; Yang, Tzu‐Yi; Sun, Yi‐Ting; et al.
Abstract : Interactions between charged amino acids significantly influence the structure and function of proteins. The encoded charged amino acids Asp, Glu, Arg, and Lys have different number of hydrophobic methylenes linking the backbone to the charged functionality. It remains to be fully understood how does this difference in the number of methylenes affect protein structure stability. Protein secondary structures are the fundamental three‐dimensional building blocks of protein structures. β‐Sheet structures are particularly interesting, because these structures have been associated with a number of protein misfolding diseases. Herein, we report the effect of charged amino acid side chain length at two β‐strand positions individually on the stability of a β‐hairpin. The charged amino acids include side chains with a carboxylate, an ammonium, or a guanidinium group. The experimental peptides, fully folded reference peptides, and fully unfolded reference peptides were synthesized by solid phase peptide synthesis and analyzed by 2D NMR methods including TOCSY, DQF‐COSY, and ROESY. Sequence specific assignments were performed for all peptides. The chemical shift data were used to derive the fraction folded population and the folding free energy for the experimental peptides. Results showed that the fraction folded population increased with increasing charged amino acid side chain length. These results should be useful for developing functional peptides that adopt the β‐conformation. Abstract : Longer charged amino acid side chain lengths at strand positions facilitate strand formation in β‐hairpins.